2023
DOI: 10.1002/cphc.202300292
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on the 1H‐NMR Chemical Shifts of Imidazolium‐Based Ionic Liquids

Abstract: The 1H nuclear magnetic resonance (1H‐NMR) spectrum is a useful tool for characterizing the hydrogen bonding (H‐bonding) interactions in ionic liquids (ILs). As the main hydrogen bond (H‐bond) donor of imidazolium‐based ILs, the chemical shift (δH2) of the proton in the 2‐position of the imidazolium ring (H2) exhibits significant and complex solvents, concentrations and anions dependence. In the present work, based on the dielectric constants (ϵ) and Kamlet‐Taft (KT) parameters of solvents, we identified that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Due to H2 being the main H-bond donor of imidazolium-based ILs, 15,16 the change of δ H2 is useful for describing the H-bonding interaction between polymers and ILs. Considering the solvent effect and concentration effect of δ H2 , 17–19 CD 2 Cl 2 is adopted as the deuterium reagent for β -type polymers/[C 4 mim][NTf 2 ] and [C 4 mim][NTf 2 ] : CD 2 Cl 2 is fixed at 1 : 500. With lower α and β values ( α = 0.13, β = 0.10), CD 2 Cl 2 will not disturb the H-bonding interaction between [C 4 mim][NTf 2 ] and β -type polymers and the δ H2 is 8.665 ppm for neat [C 4 mim][NTf 2 ] in CD 2 Cl 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to H2 being the main H-bond donor of imidazolium-based ILs, 15,16 the change of δ H2 is useful for describing the H-bonding interaction between polymers and ILs. Considering the solvent effect and concentration effect of δ H2 , 17–19 CD 2 Cl 2 is adopted as the deuterium reagent for β -type polymers/[C 4 mim][NTf 2 ] and [C 4 mim][NTf 2 ] : CD 2 Cl 2 is fixed at 1 : 500. With lower α and β values ( α = 0.13, β = 0.10), CD 2 Cl 2 will not disturb the H-bonding interaction between [C 4 mim][NTf 2 ] and β -type polymers and the δ H2 is 8.665 ppm for neat [C 4 mim][NTf 2 ] in CD 2 Cl 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Besides, our previous work found that the concentration of DMSO-d 6 also had a significant influence on δ H2 . 17 Therefore, the molar ratio of [C 4 mim][Ac] : DMSO-d 6 is increased to 1 : 14 rather than 1 : 500 to reduce the interference of DMSO on H-bonding interactions.…”
Section: Resultsmentioning
confidence: 99%
“…During the dialysis (MWCO 3500), the water-soluble small molecule by-products of the reaction leach out of the dialysis tube. The major by-product after this workup appeared to be a symmetrical protonated imidazolium ( Figure S3 ), 39 which can be converted back quantitatively to imidazole ( Figure S4 ) by the addition of NaOH and subsequently extracted in ethyl acetate. After evaporation of the solvent, pure imidazole is obtained, which can be reused for the synthesis of [Dsim]Cl.…”
Section: Resultsmentioning
confidence: 99%